EFFECT OF MAGNETIC FIELD ON WEAK MAGNETS - Nuriddinova Shahzoda Jamshid qizi; Nasirova Nargiza Gayratovna; Fayziyev Shaxobiddin Shavkatovich (Web of Journals Publishing, 2024)
This article investigates the effects of magnetic fields on weakly magnetic materials, particularly ferrites, and their influence on the physical properties of these materials. The study explores various magnetic characteristics of ferrites—ferromagnetic, paramagnetic, and antiferromagnetic—and how they change under the influence of an external magnetic field. Additionally, the article highlights the application of these changes in various fields, including electronics, medicine, electromagnetic shielding, and magnetic resonance imaging (MRI). The interaction of ferrites with magnetic fields, especially their efficiency and low-loss properties, ensures their widespread use in emerging technologies. The paper provides detailed insights into the behavior, alterations, and applications of ferrites under magnetic field influence, serving as a valuable resource for scientific research and practical applications.
Keywords: Weakly magnetic materials, ferrites, effect of magnetic fields, ferromagnetic materials, paramagnetic materials, antiferromagnetic materials, magnetic anisotropy.